POSS-tethered fluorinated diblock copolymers with linear- and star-shaped topologies: synthesis, self-assembled films and hydrophobic applications1. Issue 68 (25th July 2015) - Pan, Aizhao; Yang, Shao; He, Ling
<x xml:space="preserve">Abstract</x> Polyhedral oligomeric silsesquioxane (POSS) tethered fluorinated diblock copolymers are synthesized using octakis(dibromoethyl)POSS and aminopropylisobutyl POSS initiation of methylmethacrylate and dodecafluoroheptylmethacrylate.